EP 72. Cerebellar tDCS effects on the adaptation of arm reaching movements to force-field perturbations. Issue 9 (September 2016) - Mamlins, A.; Hulst, T.; Donchin, O.; Timmann, D.; Claaßen, J.
Abstract : Introduction: Transcranial direct current stimulation (tDCS) is a non-invasive brain-stimulation technique that can alter cortical excitability and plasticity. Previous studies have shown that anodal tDCS of the cerebellar hemispheres leads to faster adaptation of arm reaching movements to visuomotor rotation and force field perturbations in healthy subjects (Galea et al., 2011; Herzfeld et al., 2014 ). The first aim of the present study was to replicate these findings in a force field reaching adaptation task. The second aim was to investigate whether tDCS effects differ depending on onset of stimulation. Methods: 60 healthy and right-handed subjects (30 females, aged 20–31 years, mean 24.1 ± 2.3) were tested. Subjects held a two-joined manipulandum with their right hand. They moved a cursor from a central origin to one of eight targets presented on a vertical screen. Three baseline blocks were followed by one adaptation block and three post-adaptation blocks. During adaptation a velocity-dependent clockwise perpendicular force (23 N·m −1 ·s −1 ) was applied. tDCS electrodes (5 × 5 cm 2 ) were centered 3 cm lateral to the inion on the right and on the ipsilateral buccinator muscle. An equal number of subjects received anodal, cathodal or sham stimulation during adaptation using a Neuroconn® DC stimulator. tDCS started either in the third baseline block or at the beginning of the adaptation block. The maximum error, the final error and the perpendicular velocity shortly after movement onset (after 55 ms) were assessed. Results: During adaptation all subjects showed significant effects of learning. They reduced the maximum error as well as the final error and changed the sign of the perpendicular velocity shortly after movement onset ( p < 0.001, analysis of variance with repeated measures). There were no significant effects of stimulation (anodal vs. cathodal vs. sham), no significant effects of onset of stimulation (baseline vs. adaptation) and no significant interactions (all p -values > 0.05). During post-adaptation, there were significant after- and washout effects. Again, there were no significant effects of stimulation, no significant effects of onset of stimulation and no significant interactions (all p -values > 0.05). Conclusions: We were unable to replicate previous findings of modulatory cerebellar tDCS effects in a force field reaching adaptation task in healthy subjects. Furthermore, no differential effects of the onset of stimulation were observed. Prior possible application in patients with cerebellar disease, future experiments are needed to determine which tDCS and task parameters lead to robust tDCS effects. Funded by ELAN (E ssener Ausbildungsprogramm "L abor und Wissenschaft" für dena erztlichenN achwuchs) and DFG TI 239/16-1